2010
DOI: 10.1017/s0022149x10000647
|View full text |Cite
|
Sign up to set email alerts
|

Elaphostrongylus cervi in a population of red deer (Cervus elaphus) and evidence of cerebrospinal nematodiasis in small ruminants in the province of Varese, Italy

Abstract: Thirty-one faecal samples were collected from red deer in the northern area of Varese, in the Italian region of Lombardy, between August and October 2008. The animals had either been hunted or accidently killed. Examination for internal parasites showed a prevalence of 45.2% for Elaphostrongylus cervi larvae and species identification was confirmed by polymerase chain reaction (PCR). Ninety-seven faecal samples were also collected from two goat flocks grazing in the same area between December 2007 and May 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…spiculoptera morph spiculoptera , give an important contribution to composition of the community even if they have been classified into the categories of codominant or subordinate species by the importance values. In addition, the detection of a few species typical of cervids emphasizes that the goats may incur other parasitic risks resulting from interaction with these hosts on pastures [45]. Overall, a high number of helminth species is found than previous studies [46].…”
Section: Discussionmentioning
confidence: 99%
“…spiculoptera morph spiculoptera , give an important contribution to composition of the community even if they have been classified into the categories of codominant or subordinate species by the importance values. In addition, the detection of a few species typical of cervids emphasizes that the goats may incur other parasitic risks resulting from interaction with these hosts on pastures [45]. Overall, a high number of helminth species is found than previous studies [46].…”
Section: Discussionmentioning
confidence: 99%
“…Dairy goats are reared worldwide under a wide variety of management systems, ranging from intensive to extensive. In northern Italy and mainly in the pre-Alpine and Alpine environments, semi-extensive and extensive breeding systems are practiced; in this context, parasitic diseases represent an ineliminable sanitary risk, in some cases linked to sympatric wild animals (1,28). Protozoa and helminths infecting goats can impair production, inflict economic losses and, in some cases, cause zoonotic diseases (14,15,27,34).…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies abroad on E. cervi supported by both stool and necropsy examinations. (Hutsch et al 2020, Panayotova-Pencheva and Alexandrov 2011, Alberti et al 2011, Demiaszkiewicz et al 2016, Sutherland 1976, Bregoli et al 2006, Valcárcel and Garcia Romero 2002. It was reported that 16.6% of the Red deer examined in Poland were infected with Elaphostrongylus sp (Hutsch et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…E. cervi also causes neurological lesions in small ruminates. Therefore, the grazing of domesticated small ruminates in areas where deer are present indicates that the disease with a high prevalence in deer may also transmit to small ruminates (Alberti et al 2011, Handeland et al 2000. The literature research has proven that this species has not been reported in Turkey before.…”
Section: Discussionmentioning
confidence: 99%